The effectiveness of guidance groups using educational cinema techniques to increase students’ altruistic attitudes - Anggarini, Dian Junita; Ramli, M.; Rahman, Diniy Hidayatur (Journal of Research in Instructional, 2023)
Effective educational cinema techniques can be employed in group guidance sessions for junior high school students, aiming to enhance their altruistic attitudes. This study seeks to assess the efficacy of utilizing educational cinema techniques in group guidance to promote altruistic behavior among junior high school students. Employing a quantitative approach, this research adopts a quasi-experimental design with a nonequivalent control group. Purposive sampling is applied to select male and female students aged 13-14 in classes VIIIC and VIIID at SMP Negeri 2 Negara, with a focus on those demonstrating a medium-level altruistic attitude. Data collection involves construct validity and Cronbach's Alpha reliability. Descriptive analysis, encompassing mean value, standard deviation, maximum, and minimum values, is employed for data analysis. Hypothesis testing utilizes the Wilcoxon test and the Mann-Whitney test. The Wilcoxon test yields a result of 0.027 < 0.05 for both the control and experimental groups, supporting the acceptance of the hypothesis. The Mann-Whitney test reveals a result of 0.015 < 0.05, indicating a significant difference in altruistic attitudes between the experimental and control groups. In conclusion, group guidance incorporating educational cinema techniques proves effective in fostering altruistic attitudes among junior high school students.